음식료품 제조업의 온실가스 배출효율성 연구 - 강효녕; Hyonyong Kang; 서동희; Dong Hee Suh (농촌경제, 2022)
본 연구는 음식료품 제조업을 대상으로 온실가스 배출효율성과 온실가스 감축잠재량을 추정하여 음식료품 제조업의 온실가스배출 특성을 파악하고자 한다. 실증분석은 2011~2020년 19개 음식료품 제조 기업을 대상으로 시간에 따른 배출효율성의 변화를 가정한 확률변경모형을 이용하였다. 주요 연구 결과는 다음과 같다. 첫째, 음식료품 제조업의 평균 온실가스 배출효율성은 0.85로 상대적으로 높은 온실가스 배출효율성을 보였다. 둘째, 시간에 따른 음식료품 제조업의 평균 온실가스 배출효율성은 2011년 0.77에서 2020년 0.91로 향상되었다. 셋째, 대부분 음식료품 제조 기업은 탄소 저감 기술에 대한 투자로 얻을 수 있는 온실가스 감축잠재력이 상이한 것으로 나타났다. This study examines the food and beverage industry’s greenhouse gas (GHG) emission efficiency, using the stochastic frontier analysis. The results are as follows. First, the average emission efficiency of the food and beverage industry is 0.85, indicating that the food and beverage industry has relatively high technical efficiency to reduce GHG emissions. Second, the average emission efficiency increases from 0.77 to 0.91 between 2011 and 2020. It appears that the food and beverage industry has managed GHG emissions against the challenges from carbon reduction pressures. Third, regarding the GHG emission mitigation potential, the results show that most companies have different potentials for GHG reductions from investment in efficient carbon-reducing technologies.